SEASONAL SURFACE GEOSTROPHIC CURRENT IN ARAFURA-TIMOR WATERS - Fachry Ramadyan; Ivonne M. Radjawane (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2013)
Research on the seasonal geostrophic surface current during 2002-2011 in Arafura-Timor waters was conducted using satellite altimetry data. Those data were absolute dynamic topography and absolute geostrophic velocity data taken from Archiving Validation and Interpretation of Satellite Oceanographic data (AVISO). The dynamics of geostrophic surface current varied in every monsoon due to the difference in absolute dynamic topography. During  northwest (NW) season, the absolut dynamic topography in Arafura Sea was higher than in Timor Sea by an average difference of 0.1–0.2 m and the geostrophic surface current moved from Arafura Sea toward Timor Sea. During southeast (SE) season, the absolute dynamic topography in Arafura Sea lower than Timor Sea with an average difference of   0.03-0.04 m. In this season, upwelling occurs  in Banda  Sea and sea surface  water in this region  becomes  lower and  the current moved from  Arafura Sea  to Banda  Sea. The absolut dynamic topography difference between Arafura Sea and Timor Sea in NW and SE monsoons was 0.05–0.06 m and so the geostrophic surface current moved from Arafura Sea toward Timor Sea. In Timor Sea, the current moved southwest towards the Indian Ocean. In NW and SE Monsoons the the velocity of surface geostrophic current in  Timor  Sea  (0,3 m/sec) was  higher compare in Arafura Sea (0.2 m/sec)  due to the configuration of island  surround  the Timor Sea  and  its topography. Keywords: Geostrophic surface current, altimetrysatellite, Arafura-Timor Sea